2019
DOI: 10.3390/en12152981
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Solid-Gas Reactions and Their Application to Carbonate Looping Systems

Abstract: Reaction kinetics is an important field of study in chemical engineering to translate laboratory-scale studies to large-scale reactor conditions. The procedures used to determine kinetic parameters (activation energy, pre-exponential factor and the reaction model) include model-fitting, model-free and generalized methods, which have been extensively used in published literature to model solid-gas reactions. A comprehensive review of kinetic analysis methods will be presented using the example of carbonate loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 113 publications
(256 reference statements)
1
74
0
Order By: Relevance
“…Kinetic analysis of resulting individual curves, as independent reaction stages, was carried out using the linear form of Equation (5) [ 74 ]: …”
Section: Resultsmentioning
confidence: 99%
“…Kinetic analysis of resulting individual curves, as independent reaction stages, was carried out using the linear form of Equation (5) [ 74 ]: …”
Section: Resultsmentioning
confidence: 99%
“…The direct application of well-known kinetics models [ 30 ] for describing the reaction progress and rate expression faces certain difficulties related to successive reactions, altering of the physical and chemical reactivity of the remaining sample, inter-reaction between gaseous reaction products and the working sample, etc. Hence, it was suggested that the best way to evaluate the temperature impact on the chromite reactions with Cl 2 was to calculate the reaction rate in increments of 5% mass losses in the interval ranging from 5.0% to 85.0% ML.…”
Section: Resultsmentioning
confidence: 99%
“…This latter model also considers the formation of intermediate phases as concentric layers, where appropriate. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%